Pathological Spectrum of Vascular Malformations of the Central Nervous System: A Single Institution Experience of a Decade - Karanth, Shrithi; Rao, Shilpa; Savardekar, Amey; HR, Aravind; Pruthi, Nupur; Arivazhagan, Arimapamagan; Bhat, Dhananjaya I.; Srinivas, Dwarakanath; Devi, Bhagvatula Indira; Somanna, Sampath; Mahadevan, Anita (Indian Journal of Neurosurgery, 2022)
Background Vascular malformations (VMs) of the central nervous system comprise a variety of lesions that could affect the arteries, veins, or capillaries.Materials and Methods We analyzed the histopathological features of all the VMs diagnosed at our centre over a decade.Results Intracranial VM included arteriovenous malformation (AVM) (53%), cerebral cavernous malformations (CCMs) (45%), capillary telangiectasia (2%), venous angioma (0.5%), and arteriovenous fistula (AVF) (0.5%). In spinal VMs, capillary telangiectasia (40%) were the most common, followed by cavernomas (34%), AVF (16%), and AVMs and venous angiomas (5%). Clinical presentation varied from focal deficit to features of raised intracranial tension.Conclusion Imaging and histopathology plays an important role in the diagnosis and management of VMs. Histopathological examination is essential for characterization of the VMs, which influences the prognosis.
Keywords: vascular malformation; histopathology; CNS